Child and adolescent diet in Late Roman Gaul: An investigation of incremental dietary stable isotopes in tooth dentine. (18th August 2021) - Avery, L. Creighton; Brickley, Megan B.; Findlay, Sheri; Chapelain de Seréville‐Niel, Cécile; Prowse, Tracy L.
Abstract: Incremental analysis of stable carbon and nitrogen isotopes in tooth dentine is used to explore child and adolescent diet among individuals in the Late Roman Michelet Necropolis (Lisieux, France; fourth to fifth centuries CE). We analyzed 292 incremental sections from 46 second and third molars to explore dietary patterns between the ages of 4.5 and 23.5 years. Results indicate that individuals consumed more, or higher trophic level, terrestrial‐based animal proteins as they aged. Sex‐based comparisons also suggest that males and females consumed isotopically similar diets for most of their childhood; however, around age 16.5, males exhibited significantly lower δ 15 N values than females with a large effect size ( U = 21.0, p = 0.012, g = 1.3). This difference in diet occurs during an important age‐based social change in the Roman life course, as individuals transitioned from childhood ( pueritia ) to adolescence ( adulescentia ). When the isotopic data are combined with literary and archaeological evidence, it suggests that this was the point when men and women diverged in their life course trajectories. Young men were expected to begin apprenticeships or military duty away from home, whereas women were kept close to their family home at this age. The isotopic results suggest these gendered experiences may have influenced dietary choices or access to foods at Lisieux‐Michelet. The results of this study demonstrate the utility of using permanent dentition in adult remains to explore childhood experiences and provide new insights into child and adolescent diet and gendered experiences in the context of the Late Roman Empire.